Maximizing ovarian function and fertility following chemotherapy in premenopausal patients: Is there a role for ovarian suppression? - Kelsey A. Roof; Kerri E. Andre; Susan C. Modesitt; D. Austin Schirmer (Elsevier, 2024)
As more premenopausal patients undergo fertility preserving cancer treatments, there is an increased need for fertility counseling and ovarian sparing strategies. Many patients receive gonadotoxic chemotherapeutic agents which can put them at risk of primary ovarian insufficiency or profoundly diminished ovarian reserve. Traditionally, estradiol and follicle stimulating hormone (FSH) values have been used to evaluate ovarian function but more recently, reproductive endocrinologists have been proponents of anti-mullerian hormone (AMH) as a validated measure of ovarian potential. While the gold standard for fertility preservation remains oocyte cryopreservation, data suggest there may be additional interventions that can mitigate the gonadotoxic effects of chemotherapeutic agents. The main objectives of this focused review were to quantify the risk of primary ovarian failure associated with the most common chemotherapies used in treatment of gynecologic cancers and to evaluate and recommend potential interventions to mitigate toxic effects on ovarian function. Chemotherapeutic agents can cause direct loss of oocytes and primordial follicles as well as stromal and vascular atrophy and the extent is dependent upon mechanism of action and age of the patient. The risk of ovarian failure is the highest with alkylating agents (42.2 %), anthracyclines (<10-34 % in patients under 40 years versus 98 % in patients aged 40-49), taxanes (57.1 %) and platinum agents (50 %). Multiple trials demonstrate that gonadotropin releasing hormone (GnRH) agonists, when administered concurrently with chemotherapy, may have protective effects, with more patients experiencing resumption of a regular menstruation pattern and recovering ovarian function more quickly post-treatment. Premenopausal patients receiving chemotherapy for the treatment of gynecologic cancers should receive adequate counseling on the potential adverse effects on their fertility. Although oocyte cryopreservation remains the gold standard for fertility preservation, there is some evidence to suggest that GNRH agonists could help maintain and preserve ovarian function and should be considered.